Water Quality Control System Based on Web Application for Monitoring Shrimp Cultivation in Sidoarjo, East Java - Arna Fariza; Setiawardhana Setiawardhana; Bima Sena Bayu Dewantara; Aliridho Barakbah; Dadet Pramadihanto; Idris Winarno; Tessy Badriyah; Tri Harsono; Iwan Syarif; Wahjoe Tjatur Sesulihatien; Puspasari Susanti; Achmad Thorikul Huda; Oktavia Citra Resmi Rachmawati; Izza Nur Afifah; Rudi Kurniawan; Silfiana Nur Hamida (Universitas Nurul Jadid, 2023)
Shrimp farming plays a crucial role to the Indonesian economy, but it is facing challenges from shifting weather patterns and global warming. This research focuses on the development and implementation of a web-based water quality monitoring system for shrimp farming to address these concerns. The research, conducted in collaboration with shrimp farmers in Sidoarjo, East Java, introduces PENS Aquaculture program, which is designed to efficiently monitor pH, salinity, and temperature. The system employs Internet ofThings (IoT) technology, which allows farmers to register several ponds, analyze water parameters, and receive real-time data through tables and graphs. The research takes a mixed-methods approach, integrating quantitative data from IoT devices with qualitative insights gathered through surveys and interviews with shrimp farmers. The study aims to evaluate the influence of IoT technology on shrimp pond quality and its contribution to the production. The findings show that PENS Aquaculture application is helpful in increasing shrimp farming efficiency, providing significant insights for the fisheries and cultural sectors.